Deng Xiaoping and the transformation of China - Vogel, Ezra F. (Cambridge Belknap Press of Harvard University Press, 2011)
No one in the twentieth century had a greater impact on world history than Deng Xiaoping. And no scholar is better qualified than Ezra Vogel to disentangle the contradictions embodied in the life and legacy of China's boldest strategist-the pragmatic, disciplined force behind China's radical economic, technological, and social transformation.
Includes bibliographical references and index.
Keywords: Deng, Xiaoping, 1904-1997.